Cross-sectional study of the factors predisposing to obstructive sleep apnea in the adult population attending ENT outpatient department with snoring in tertiary care center - Puthukudy, Preetham A.; Feshan, Musarrat; Arumugasamy, Rathipriya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Obstructive sleep apnea (OSA) is characterized by repetitive upper airway obstruction leading to stimulation of the cardiovascular system, oxygen desaturation, and sleep fragmentation. Overnight polysomnography (PSG) is the standard diagnostic test for Obstructive sleep apnea. The objective of the study was to assess the prevalence and severity of OSA and the factors predisposing to OSA. Methods: In this cross-sectional study, 98 patients with snoring were subjected to undergo polysomnography. Apnea-hypopnea index (AHI), Oxygen desaturation events per hour, and Lowest oxygen desaturation events per hour were statistically analyzed. The Chi-square test and analysis of variance (ANOVA) test were used and the p value was calculated. Statistical package for the social sciences (SPSS) version 20 was used for statistical analysis. Results: In our study, the most common age group affected was between 51-60 years. The most common comorbidity found among the patients was hypertension. There was a positive correlation between OSA and neck circumference. The most common type of apnea was obstructive apnea. AHI was found to have a positive correlation with OSA and its severity. There was a significant association between average oxygen desaturation and OSA. There was also a positive correlation between ODI and OSA. Conclusions: Increasing age, neck circumference, deviated nasal septum, and inferior turbinate hypertrophy had a strong association with OSA. Polysomnography shows the strong association of AHI, and oxygen desaturation events per hour with OSA.